2007
DOI: 10.1016/j.jinorgbio.2006.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium distribution, lipid peroxidation and oxidative stress markers upon decavanadate in vivo administration

Abstract: The contribution of decameric vanadate species to vanadate toxic effects in cardiac muscle was studied following an intravenous administration of a decavanadate solution (1 mM total vanadium) in Sparus aurata. Although decameric vanadate is unstable in the assay medium, it decomposes with a half-life time of 16 allowing studying its effects not only in vitro but also in vivo. After 1, 6 and 12 h upon decavanadate administration the increase of vanadium in blood plasma, red blood cells and in cardiac mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
111
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(121 citation statements)
references
References 30 publications
10
111
0
Order By: Relevance
“…Decavanadate solutions were obtained by adjusting the pH of the metavanadate solution to 4.0. 14, 29 The presence of decameric vanadate species was revealed by a characteristic orange color. Decavanadate solutions were always adjusted to pH 7.5 immediately before using.…”
Section: Preparation Of "Metavanadate" "Decavanadate" and Vanadyl Somentioning
confidence: 99%
See 2 more Smart Citations
“…Decavanadate solutions were obtained by adjusting the pH of the metavanadate solution to 4.0. 14, 29 The presence of decameric vanadate species was revealed by a characteristic orange color. Decavanadate solutions were always adjusted to pH 7.5 immediately before using.…”
Section: Preparation Of "Metavanadate" "Decavanadate" and Vanadyl Somentioning
confidence: 99%
“…The kinetics were followed for 120 min at different temperatures. Since the V 10 dissociation follows a firstorder reaction kinetics, 29 it was possible to determine the activation energy (E a ) for the dissociation.…”
Section: Uv-visible Characterization Of Decavanadate Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Decameric vanadate, composed by fused V(V) octahedra, has an ellipsoid like structure with a major and minor axis of approximately 7 and 6 Å , respectively [1]. In previous studies [2][3][4][5][6][7][8], we have demonstrated that once formed in aqueous solutions decameric vanadate decomposition is slow enough to allow studying differential effects between decameric and monomeric vanadate not only in vitro but also in vivo. Furthermore, decameric vanadate is stabilized upon interaction with cytoskeleton and membrane proteins, while it affects calcium translocation by the sarcoplasmic reticulum calcium pump and it prevents actin polymerization [9].…”
Section: Introductionmentioning
confidence: 99%
“…When pH and V concentration are changed from the thermodynamically favourable ones it decomposes with a very slow kinetics [34,47]. Like the monomeric species, decavanadate (V10) does not show any activity in the absence of an activating agent (Fig.…”
Section: Dna Cleavage By V Iv O(acac) 2 Related Derivativesmentioning
confidence: 99%